ANALISIS KEMAMPUAN MEMBACA LANJUTAN DITINJAU DARI POLA ASUH DEMOKRATIS SISWA KELAS III SD BAWAMAI PONTIANAK KOTA - a, Nabila Bila (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study analyzes the relationship between democratic parenting styles at home and the advanced reading abilities of third-grade students at SD BAWAMAI, Pontianak Kota. Despite adequate school facilities, some students show weak reading skills, suggesting parental influence as a key factor. Using a descriptive qualitative approach, data were collected through observations, reading tests, interviews, and parent questionnaires. Findings show that children raised with democratic parenting"”marked by open communication, acceptance, and responsive guidance"”demonstrate stronger reading skills, including critical comprehension and contextual reading pace. The study highlights the vital role of parental involvement in fostering literacy and the need for a supportive home reading environment.